An Efficient Scheduling Algorithm for Garbage Monitoring System Using RTOS - et. al, V. Mallikharjuna Rao (International Journal of Advanced Science and Technology, 2020)
Environment Condition around us ought to be sound since it is fundamental to a strong and happy society.With the profound established course of action of acquiring people to frequently verify and release overflowing garbage storage bins, the method has been slanted to human mistake and negligence. Additionally, on account of a different repeat of usage dustbins in various places, schedule checks which rely upon the time gap are inefficient. Sometimes it is a fact that a dustbin may get filled early and may require brief thought or there presumably won't be any need of a typical check for a noteworthy parcel of time. Many old systems are concentrated on different types of scheduling methods for the Garbage Trucks but they are not concentrated on the system performance.  In this paper, normally utilized solutions for enhance waste gathering frameworks have been discussed and an IoT Non-blocking framework configuration based approach has been proposed as another solution.